PENGARUH KEPEMILIKAN INSTITUSIONAL, MAKRO EKONOMI, INVESTMENT OPPORTUNITY SET TERHADAP NILAI PERUSAHAAN (Studi Kasus Pada Badan Usaha Milik Negara Sector Perbankan Periode 2014-2016) - Umbaran, Dita Faradhila; Rachmawati, Titiek (JEA17: Jurnal Ekonomi Akuntansi, 2020)
ABSTRACTThis study aims to determine the effect of Institutional Ownership, Macro Economic, Investment Opportunity Set Against Corporate Value "(Case Study On State- Owned Enterprises Banking Sector Period 2014-2016)". Hypothesis in this research is institutional ownership, macro economy, investment opportunity set. This study uses secondary data that is the annual financial statements (Annual Report) listed on the Indonesia Stock Exchange (BEI). Population in this research is all company of banking sector of special finance of BUMN listed in Indonesian Stock Exchange (BEI) year 2014-2016 as many as 4 company for 3 years. Based on Nonprobability Sampling method, sampling technique in this research use saturated sampling technique where all members of the population are sampled. The data retrieval technique used in this research is documentation and literature study. Data analysis technique used is Partial Least Square (PLS). The result of the analysis shows that the variable of institutional ownership have significant effect to firm value, macro economy have significant effect to company value, and investment opportunity set have significant effect to firm value.From the results of this study can be concluded that institutional ownership, macro economic, investment opportunity set significant effect on corporate value. The researcher's suggestion for further research is expected to be done in other sectors, such as manufacturing, service companies or all companies listed on BEI. It is possible to give results comparative influence of previous research. From the results of research for investors is expected to provide information for the management of companies and shareholders in the relationship agency problems.